1989
DOI: 10.1172/jci114365
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 metabolites of arachidonic acid are potent inhibitors of vasopressin action on rabbit cortical collecting duct.

Abstract: AA is metabolized by a cytochrome P450, NADPH-dependent epoxygenase to four regioisomeric epoxyeicosatrienoic acids (EETs). The EETs are further hydrated enzymatically to their respective diols, vic-dihydroxyeicosatrienoic acids (DHETs). We studied the effect of pretreatment with DHETs on 10 ,gU/cm2 arginine vasopressin (AVP)-stimulated hydraulic conductivity (Lp) (Lp X 10' cm/atm/s, mean±SE) in rabbit cortical collecting ducts (CCDs) perfused in vitro at 370C. At 10-6 M all four DHETs were potent inhibitors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…4,31 EETs have also been reported to inhibit Na ϩ /K ϩ -ATPase activity, 32 inhibit Na ϩ transport in the proximal tubule 33 and rabbit cortical collecting duct, 7 and inhibit vasopressin-stimulated water reabsorption in the collecting duct. 6 20-HETE also plays a critical role in the regulation of Cl Ϫ transport in the TALH 3,5 and inhibits Na ϩ /K ϩ /2Cl -transport by blocking K ϩ channels in the apical membrane of TALH cells, 34 thereby limiting the availability of K ϩ for transport via Na ϩ /K ϩ /2Cl Ϫ transporters. This reduces the lumen positive transepithelial potential and reduces passive reabsorption of Na ϩ in this nephron segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,31 EETs have also been reported to inhibit Na ϩ /K ϩ -ATPase activity, 32 inhibit Na ϩ transport in the proximal tubule 33 and rabbit cortical collecting duct, 7 and inhibit vasopressin-stimulated water reabsorption in the collecting duct. 6 20-HETE also plays a critical role in the regulation of Cl Ϫ transport in the TALH 3,5 and inhibits Na ϩ /K ϩ /2Cl -transport by blocking K ϩ channels in the apical membrane of TALH cells, 34 thereby limiting the availability of K ϩ for transport via Na ϩ /K ϩ /2Cl Ϫ transporters. This reduces the lumen positive transepithelial potential and reduces passive reabsorption of Na ϩ in this nephron segment.…”
Section: Discussionmentioning
confidence: 99%
“…1 20-Hydroxyeicosatetraenoic acid (20-HETE) inhibits Na ϩ transport in the proximal tubule and thick ascending limb of the loop of Henle (TALH), [2][3][4][5] and compounds that induce the renal formation of 20-HETE lower blood pressure in Dahl salt-sensitive (DS) rats. 1 Similarly, epoxyeicosatrienoic acids (EETs) inhibit Na ϩ transport in the proximal tubule and collecting duct, 6,7 and increasing the renal levels of EETs with inhibitors of soluble epoxide hydrolase (sEH) reduces blood pressure in spontaneously hypertensive rats (SHRs) 8 and angiotensin II-induced hypertensive rats. 9 However, 20-HETE is also a potent vasoconstrictor, 1 and many investigators have reported that blocking the vascular effects of 20-HETE may contribute to its antihypertensive effect in SHR and other experimental models of hypertension.…”
mentioning
confidence: 99%
“…The demonstrated abilities of EETs to directly activate smooth muscle K ϩ channels (21) and to inhibit the renal Na ϩ -K ϩ -ATPase (22,23) are potential mechanisms by which the vasodilatory and antihypertensive actions of EETs may be achieved. In the rabbit cortical collecting duct, 14,15-DHET is a potent inhibitor of vasopressin-stimulated water reabsorption (24) and inhibits osmotic water flow in the toad urinary bladder (25). Dietary salt loading of rats causes increased urinary excretion of EETs and DHETs concomitant with induction of renal CYP-dependent epoxygenase activity (9,26).…”
mentioning
confidence: 99%
“…Indomethacin, A23187, and L-ascorbic acid were purchased from Sigma (St. Louis, MO). C 18 Bond Elut solid-phase extraction (SPE) columns were purchased from Varian (Harbor City, CA). Acetonitrile was HPLC grade.…”
Section: Methodsmentioning
confidence: 99%
“…Cytochrome P450 epoxygenases metabolize AA to 4 regioisomeric epoxyeicosatrienoic acids (EETs), and soluble epoxide hydrolase (sEH) enzymes subsequently convert EETs to the corresponding DHETs [15][16][17]. EETs have various biological functions, including inhibiting the hydro-osmotic action of arginine vasopressin in the kidney, calcium mobilization, and prostaglandin formation [18,19]. EETs stimulate relaxation in coronary rings and coronary arterioles [20 -25].…”
mentioning
confidence: 99%